Lessons learned from breast implant registries: a systematic review - Wurzer, Paul; Hundeshagen, Gabriel; Cambiaso-Daniel, Janos; Fischer, Sebastian; Hoflehner, Helmut; Spendel, Stephan; Lumenta, David; Kamolz, Lars; Kneser, Ulrich; Hirche, Christoph (Annals of plastic surgery, 2019)
ObjectiveOver several decades, numerous national and international registries on breast implants went online, aiming to collect prospective data to provide increased safety for patients and surgeons. We performed a review of all published data on breast implant registries to assess availability and
Gesehen am 29.01.2020